Effects of Bartter's syndrome on dentition and dental treatment: A clinical report - GÖZNELİ, RİFAT; ÖZKAN, YASEMİN (MOSBY-ELSEVIER, 2005)
Bartter's syndrome is an autosomal recessive form of severe volume depletion due to renal salt wasting. This clinical report describes the prosthodontic treatment for a 24-year-old man who suffers from Bartter's syndrome. The treatment plan included endodontic treatment of the maxillary anterior incisors and placement of cast dowel-and-core restorations because of reduced crown height. The patient's remaining teeth were restored with metal-ceramic crowns.
Keywords: CANINE-PROTECTED SPLINT; EATING DISORDERS; GITELMANS-SYNDROME; BULIMIA